COMPYTER SYSTEMS SECURITY - Kubarenko, Anna; Grabusts, Pēteris (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2016)
The author in this work provides insight into computer systems security. Themes which are discussed is hardware security, logical security, viruses and computer protection. Nowadays computers are a part of daily life, so each user how to know how to protect computer and its data.